Developing STEM-Based Student Worksheet to Improve Students’ Creativity and Motivation of Learning Science - Emi Fitrya Husna; Muhammad Adlim; Abdul Gani; Muhammad Syukri; Muhammad Iqbal (Tadris Biologi Fakultas Ilmu Tarbiyah dan Keguruan IAIN SYEKH NURJATI CIREBON, 2020)
The Student worksheet based on science, technology, engineering, and mathematics (STEM) has been prepared, validated, and tested on students at SMAN 5 Banda Aceh. The worksheet guided the students to design a salt-making tool with a sunlight-gathering mirror. The worksheet was developed using the ADDIE model of the research and development (R&D) method. The subjects of the study consisted of 31 students divided into some groups consisting of 6 participants for each. The students were given problems and examples of salt-producing tools using a sunlight-collecting mirror. The purpose of this activity was to let them observe and modify according to their creativity. Based on the assessment of the tool model produced by students, the gained score reached an average score of 91 (very good). After the learning process, the learning outcomes increased with an average of 42 to 70. The science learning motivation and creativity scores of the students after the implementation reached 76 (good) and 79 (good).